2021
DOI: 10.1186/s12865-021-00430-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CD27 expression on T-cells as a diagnostic and therapeutic tool for patients with smear-negative pulmonary tuberculosis

Abstract: Background There is a global focus on illness diagnosis in smear-negative and latent tuberculosis infectious populations (SN-TB and LTBI). CD27 has been suggested to play a direct role in active TB. Little is known about smear-negative individuals. Here, we tried to investigate whether it has a role in smear-negative populations. The expression of CD27 and MTB-specific CD27 in CD4+ T cells (“CD27−CD4+” and “CD27−IFN-γ+CD4+”) was evaluated in MTB-unexposed controls (HC), TB contacts (TB-C) and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In recent years, the research on T cell-related molecular markers has been a hot topic. Xu et al [24] evaluated CD27 in CD27 − IFN-γ + CD4 + T cells for differential diagnosis in TB-unexposed healthy people, TB contacts, and smear-negative TB and concluded that the percentage of CD27 − IFN-γ + CD4 + cells can distinguish smear-negative TB patients from the other two groups (AUC = 0.88, sensitivity 82.1%, speci city 80.0%). The study focused on the differential diagnosis of sputum smear-negative ATB and LTB, but many of the smear-negative patients were culture-positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the research on T cell-related molecular markers has been a hot topic. Xu et al [24] evaluated CD27 in CD27 − IFN-γ + CD4 + T cells for differential diagnosis in TB-unexposed healthy people, TB contacts, and smear-negative TB and concluded that the percentage of CD27 − IFN-γ + CD4 + cells can distinguish smear-negative TB patients from the other two groups (AUC = 0.88, sensitivity 82.1%, speci city 80.0%). The study focused on the differential diagnosis of sputum smear-negative ATB and LTB, but many of the smear-negative patients were culture-positive.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that compared with LTBI, CD27 − and CD38 + are mainly expressed in ATB and could be used as markers to distinguish the two diseases [22][23][24], but there are few studies on the combined CD27 − and CD38 + pro le. Therefore, this study aimed to detect the co-expression of CD27 and CD38 molecules in CD4 + and CD4 + IFN − γ + T cells and investigate the accuracy of CD27 − CD38 + IFN-γ + CD4 + /CD4 + and other MTBspeci c phenotypic markers for ATB diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have analyzed the changes of CD27 and CD38 in T cell during anti-TB treatment. Xu et al found that the percentage of CD27 -IFN-γ + CD4 + cells was signi cantly decreased after 3and 6-months of anti-TB treatment [13]. Ahmed et al [20] demonstrated that the frequencies of activation marker CD38 + were signi cantly decreased, while the frequencies of CD27was largely unchanged until week 26 [21].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have looked at M.tb -specific TNF producing CD4 + T cells along with the detection of M.tb -specific CD8 + T cells and found that, in combination, these immunological assays have a 81.1% sensitivity and 86.5% specificity in the diagnosis of active TB ( 90 92 ). Active TB is also significantly associated with an increase in CD27- M.tb -specific CD4+ T cells, where evaluating CD27+ CD45RA- CD4+ IFN-γ + T cells increases diagnostic accuracy of active TB vs. cured TB or LTBI even further ( 93 ). Indeed, the combination of different blood biomarkers – namely, CD27, CD45RA, and TNF – within the population of CD4 + IFN-γ + T cells provides a good acceptable diagnostic accuracy regarding active TB vs. LTBI with 92% sensitivity and 97% specificity while reducing the need to obtain a sputum sample ( 93 ).…”
Section: Tb Immunodiagnostic Testsmentioning
confidence: 99%
“…Active TB is also significantly associated with an increase in CD27- M.tb -specific CD4+ T cells, where evaluating CD27+ CD45RA- CD4+ IFN-γ + T cells increases diagnostic accuracy of active TB vs. cured TB or LTBI even further ( 93 ). Indeed, the combination of different blood biomarkers – namely, CD27, CD45RA, and TNF – within the population of CD4 + IFN-γ + T cells provides a good acceptable diagnostic accuracy regarding active TB vs. LTBI with 92% sensitivity and 97% specificity while reducing the need to obtain a sputum sample ( 93 ). Notably, however, these improvements in immunodiagnostics are not POC and do not allow for the detection of DS- vs. DR-TB cases within a population of individuals that have active TB, regardless of their HIV status.…”
Section: Tb Immunodiagnostic Testsmentioning
confidence: 99%